Customer perception towards Bumiputera's SME products in Medan MARA, Kuala Lumpur / Wan Khalidah Aqilah Wan Mohd Zulkifli - Wan Mohd Zulkifli, Wan Khalidah Aqilah (2017)
The study aims to identify the factors that can lead to the satisfaction of customers towards the Bumiputera's SME products and to determine the main attribute that coexist with the variables that contribute to the customers' perception towards the Bumiputera's SME products. The issues that arises in this study are packaging, quality and price sensitivity of the products. 50 customers had been selected as a respondents due to the constraint time and willingness of respondents to reply correctly and willingly. Moreover, before the questionnaire being distributed to the respondents a sample of 5 customers were selected to complete a pilot test study as to improve the study. Using convenience sampling, the questionnaires are distributed to customers that come in the Medan MARA. Therefore, throughout the research findings, there's only has one hypothesis were supporting the research. Overall, brand image has a major influences for customer to purchase the Bumiputera's SME products.